Cryptosporidiosis in pigeons - Oliveira, Bruno César Miranda [UNESP]; Ferrari, Elís Domingos [UNESP]; Nagata, Walter Bertequini [UNESP]; Inácio, Sandra Valéria [UNESP]; Da Cruz Panegossi, Mariele Fernanda [UNESP]; Corbucci, Flávio Sader [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2017)
Pigeons are widely distributed in the cities, where usually they look for places like hen houses, public parks, school yards, farms and gardens to feed themselves, because at these places there is a lot of food with easy access, they can find materials to build their nests and with no natural predators they have adapted easily and their population is increasing in the cities. Nowadays they are considered sinantropic animals widely distributed on the cities, representing a severe environmental issue to an, since they host and disseminate some parasites that can be harmful to the human health like the Cryptosporidium spp. The protozoa of the gender Cryptosporidium is an intracellular parasites that develops in the microvilli of the epithelial cells of the gastrointestinal, respiratory and urinary tract of mammals, birds, reptiles and fishes. In birds, the cryptosporidiosis represents one of the main protozoosis, with symptomatology that involves the respiratory or digestive tract, being reported in more than 30 species of various orders including the Columbiformes. Approximately 30 genotypes of Cryptosporidium that affect birds are described. This chapter has the objective to elucidate epidemiological aspects and to approach about the infection by Cryptosporidium in pigeons.
Keywords: Columbiforme; Cryptosporidiosis; Epidemiological